A new combination in Angraecoides (Angraecinae, Orchidaceae): a forgotten name - Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2016)
A new nomenclatural combination for the African species Angraecum moandense to the recently proposed genus Angraecoides is provided. Angraecum chevalieri is confirmed as a synonym of this species.